Sprint force-velocity profiles in soccer players: impact of sex and playing level - Devismes, M.; Aeles, J.; Philips, J.; Vanwanseele, B. (Sports Biomechanics, 2019)
This study aimed to assess potential differences in force-velocity (Fv) profiles in both male and female soccer players of different playing levels. One hundred sixty three soccer players (63 women and 100 men) competing from the Regional to the National Belgian league were recruited. The participants performed two maximal 60-m sprints monitored via a 312 Hz laser. For each participant, the theoretical maximal force (F0) and velocity (v0), maximal power (Pmax), maximal ratio of force (RF) and the slope of the Fv profile (Sfv) were computed. Male players in the highest competition level showed higher values for all the Fv variables compared to lower level groups (Effect size range: 1.01-1.97). Higher Pmax and v0 were observed in the female players of highest competition level compared to all other groups (ES range: 1.09-1.48). Female players showed more negative Sfv than male players (ES = 1.11), which suggests that male players` Fv profile is more velocity-oriented compared to female players. This study shows that the determinants of sprint performance increase with soccer playing level in both men and women, but that the contribution of each variable varies with sex.